Interpretasi Simbolik Pada Tradisi Bubakan Dalam Relasi Hukum Islam Dan Budaya Lokal Perspektif Clifford Geertz - Sukma Arohman Putra; Agus Purnomo; Abid Rohmanu (Institut Agama Islam Negeri Ponorogo, 2025)
The Bubakan tradition is one of the ceremonial sequences in Javanese wedding rituals, rich in symbolic elements and philosophical meaning, particularly as a form of purification and preparation intended to open the life path of the bride and groom so they may avoid obstacles and receive blessings. This study aims to uncover the symbolic meanings embedded in each element of the Bubakan tradition and to understand its role in reinforcing the social, spiritual, and cultural values of Javanese society. This research is a field study employing a qualitative–ethnographic approach. Data were collected through participant observation and in-depth interviews with traditional leaders, ritual practitioners, and community members involved in the ceremony. The study was conducted within Javanese communities that continue to preserve the Bubakan tradition. The collected data were analyzed using descriptive and analytical techniques with an inductive reasoning pattern and verification. The analysis adopts Clifford Geertz’s anthropological perspective, which views culture as a system of meanings expressed through symbols. The findings show that each element of the Bubakan tradition—such as the tumpeng, white cloth, offerings, and ritual movements—possesses profound symbolic significance representing blessings, hopes for a harmonious new life, purity of intention, and familial unity. The tradition also reflects Javanese cultural philosophy, emphasizing balance, harmony, and spirituality. The study concludes that the Bubakan tradition is not merely a ceremonial ritual but a symbolic representation of Javanese cultural values that continue to endure and remain meaningful within contemporary artistic practice.